Facile one‑pot synthesis of water‑soluble fcc FePt3 alloy nanostructures - Kizaloğlu Akbulut, Melek; Harreiß, Christina; Löffler, Mario; Mayrhofer, Karl J.J.; Schöbitz, Michael; Bachmann, Julien; Spiecker, Erdmann; Hock, Rainer; Kryschi, Carola (SN Applied Sciences, 2020)
Proccessible FePt3 alloy nanoparticles with sizes smaller than 50 nm open the avenue to novel magnetic sensor, catalytic and biomedical applications. Our research objective was to establish a highly scalable synthesis technique for production of single-crystalline FePt3 alloy nanoparticles. We have elaborated a one-pot thermal decomposition technique for the synthesis of superparamagnetic FePt3 nanoparticles (FePt3 NPs) with mean sizes of 10 nm. Subsequent tiron coating provided water solubility of the FePt3 NPs and further processibility as bidental ligands enable binding to catalyst surfaces, smart substrates or biosensors. The chemical composition, structure, morphology, magnetic, optical and crystallographic properties of the FePt3 NPs were examined using high resolution transmission electron microscopy, high angle annular dark field-scanning transmission electron microscopy, scanning transmission electron microscopy-energy-dispersive X-ray spectroscopy mapping, Fourier transform infrared-attenuated total reflection, X-ray powder diffraction, X-ray photoelectron spectroscopy, vibrating sample magnetometry and UV–Vis absorption spectroscopy.<br
Keywords: Iron-platinum alloy; FePt3 nanoparticles; XPS; XRD analysis; Thermal decomposition route